CRITICAL AUTOETHNOGRAPHY AND THE VULNERABLE SELF AS RESEARCHER - Tilley-Lubbs, Gresilda A. (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2015)
This paper presents critical autoethnography as an innovative approach to conducting research in marginalized, vulnerable communities. Combining autoethnography, ethnography, and critical pedagogy, the researcher becomes a participant in the study, turning inward to examine the Self and the complexities of cultural perspectives through the lens of critical pedagogy. Intense reflexivity and introspection undergird this study of Self as participant, going beyond recounting facts as objectively as possible, as occurs with autobiography, to acknowledging that the researcher is interpreting the facts through cultural perspectives formed through years of sociocultural, socio-historical, sociopolitical, and socioeconomic events and circumstances. Subsequently, the researcher, more than likely a member of the dominant culture in some categories is able to understand herself as an oppressor.